Commercial Disinfectants During Disinfection Process Validation: More Failures than Success - Chatterjee, Shiv Sekhar (J Clin Diagn Res, 2016)
INTRODUCTION: Disinfection process validation is mandatory before introduction of a new disinfectant in hospital services. Commercial disinfection brands often question existing hospital policy claiming greater efficacy and lack of toxicity of their products. Inadvertent inadequate disinfection leads to morbidity, patient’s economic burden, and the risk of mortality. AIM: To evaluate commercial disinfectants for high, intermediate and low-level disinfection so as to identify utility for our routine situations. MATERIALS AND METHODS: This laboratory based experiment was conducted at St Stephen Hospital, Delhi during July-September 2013. Twelve commercial disinfectants: Sanidex®, Sanocid®, Cidex®, SekuSept Aktiv®, BIB Forte®, Alprojet W®, Desnet®, Sanihygiene®, Incidin®, D125®, Lonzagard®, and Glutishield® were tested. Time-kill assay (suspension test) was performed against six indicator bacteria (Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Salmonella Typhi, Bacillus cereus, and Mycobacterium fortuitum). Low and high inoculum (final concentrations 1.5X10(6) and 9X10(6) cfu/ml) of the first five bacteria while only low level of M. fortuitum was tested. RESULTS: Cidex® (2.4% Glutaraldehyde) performed best as high level disinfectant while newer quarternary ammonium compounds (QACs) (Incidin®, D125®, and Lonzagard®) were good at low level disinfection. Sanidex® (0.55% Ortho-pthalaldehyde) though mycobactericidal took 10 minutes for sporicidal activity. Older QAC containing BIB Forte® and Desnet® took 20 minutes to fully inhibit P. aeruginosa. All disinfectants effectively reduced S. Typhi to zero counts within 5 minutes. CONCLUSION: Cidex® is a good high-level disinfectant while newer QACs (Incidin®, D125®, and Lonzagard®) were capable low-level disinfectants.